Bacillus Calmette–Guérin–induced interleukin‐10 inhibits S100A8/A9 production and hinders development of T helper type 1 memory in mice. Issue 4 (16th February 2023) - Wang, Yaping; Sun, Yuehua; Zheng, Yong; Yang, Yuling; He, Liu; Qu, Peijie; Zhou, Fangting; Xu, XiaoXu; Bai, Xuanchang; Chen, Xin; Yuan, Yangxuan; Liu, Min; et al.
Abstract: Tuberculosis caused by Mycobacterium tuberculosis (M.tb) is one of the main causes of human death in the world. Bacillus Calmette‐Guérin (BCG) provides limited protection in adolescents and adults. To explore the factors reducing efficacy of BCG vaccine, we assess the impacts of interleukin (IL)‐10 and alarmins S100A8/A9 on T‐cell memory. We found that BCG‐induced IL‐10 inhibited production of S100A8/A9 in human peripheral blood mononuclear cells (PBMCs) and murine splenocytes. S100A9 deficiency inhibited IFN‐γ production by CD4 + T cells in the early phase of BCG immunization and hindered the development of effector memory T helper type 1 (Th1) cells, while IL‐10 deficiency promoted Th1 memory and blocking IL‐10 signaling enhanced Th1 protective recall response against M.tb . IL‐10 inhibited the binding of transcription factor CCAAT enhancer binding protein beta to S100a8/a9 promoter leading to S100A8/A9 reduction. S100A8/A9 heterodimer enhanced the IFN‐γ production via receptor for advanced glycation end products signaling in CD4 + T cells. Our results demonstrate a hurdle to development of Th1 memory after BCG immunization and clarify the mechanism of the regulation of Th1 memory by IL‐10 and S100A8/A9. Abstract : BCG‐induced IL‐10 inhibits production of alarmins S100A8 and S100A9 in human PBMCs and murine splenocytes. BCG‐induced Th1 memory is dampened by IL‐10 and decreased S100A8/A9. Blocking IL‐10 signaling enhances Th1 protective recall response against Mycobacterium tuberculosis . Our report elucidates the mechanism of the regulation of Th1 memory by IL‐10 and S100A8/A9.